2015
DOI: 10.1002/cdq.12032
|View full text |Cite
|
Sign up to set email alerts
|

Neuroticism, Negative Thinking, and Coping With Respect to Career Decision State

Abstract: Using structural equation modeling, the present study investigated relationships between neuroticism, coping strategies, and negative career thoughts within the context of attaining a positive career decision state. Results from the initial model, based on a sample of college students (119 women, 113 men; M = 20.3 years) enrolled in a career development course, revealed that coping strategies were not a significant contribution to the model. The final model, without coping strategies, showed that neuroticism h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
1
13
0
1
Order By: Relevance
“…Convergent validity was demonstrated through correlations between the CSI total score and the Career Thoughts Inventory (Sampson, Peterson, Lenz, Reardon, & Saunders, 1996) total score ( r = .63, p < .001), Decision‐Making Confusion subscale ( r = .63, p < .001), Commitment Anxiety subscale ( r = .60, p < .001), and External Conflict subscale ( r = .42, p < .001). Previous studies have used the CSI and found it an adequate measure of career decision state (Bullock‐Yowell et al, 2015; Miller et al, 2018). In the current study, internal consistency estimates (coefficient alpha) for the CSI total score at pretest were .70 for those in the CD course and .77 for those in the HR course.…”
Section: Methodsmentioning
confidence: 99%
“…Convergent validity was demonstrated through correlations between the CSI total score and the Career Thoughts Inventory (Sampson, Peterson, Lenz, Reardon, & Saunders, 1996) total score ( r = .63, p < .001), Decision‐Making Confusion subscale ( r = .63, p < .001), Commitment Anxiety subscale ( r = .60, p < .001), and External Conflict subscale ( r = .42, p < .001). Previous studies have used the CSI and found it an adequate measure of career decision state (Bullock‐Yowell et al, 2015; Miller et al, 2018). In the current study, internal consistency estimates (coefficient alpha) for the CSI total score at pretest were .70 for those in the CD course and .77 for those in the HR course.…”
Section: Methodsmentioning
confidence: 99%
“…A significant relationship between neuroticism (i .e ., a general tendency to experience negative effects such as fear, sadness, embarrassment, anger, guilt, and disgust; Costa & McCrae, 1992, p . 14) and career decision state via negative career thinking has also been indicated (Bullock-Yowell, Reed, et al ., 2015) .…”
Section: Career Decision State and Negative Career Thinkingmentioning
confidence: 95%
“…A literatura para justificar esses resultados é escassa, porém, ao considerar outros fenômenos psicológicos subjacentes (ex., traços de personalidade), pode-se encontrar explicações iniciais para essas diferenças, como a relação entre pensamentos negativos e o traço neuroticismo (Bullock-Yowell et al, 2015;Kelly & Shin, 2008). De acordo com Wille, De Fruyt e Feys (2013) em estudo cobrindo entrada e estabelecimento no mercado de trabalho, foram encontradas diferenças entre os sexos para o fator neuroticismo, no qual mulheres apresentaram indicadores superiores nesse traço, além de maior conflito trabalho-família.…”
Section: Valores Dos Betas Padronizados E Dos Z-escores Para As Análiunclassified